REKONSTRUKSI DASAR TEOLOGI PENDIDIKAN ISLAM DALAM MENGHADAPI TANTANGAN ERA DIGITAL: Indonesia - Rizki Imanudin; Dayat Indra Hidayat; Dede Sulaeman; Adang Hambali; Andewi Suhartini (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
The rapid development of digital technology has significantly transformed the landscape of education, creating new opportunities as well as complex challenges such as information distraction, individualistic tendencies, and a crisis of meaning among learners. This study aims to reconstruct the theological foundations of Islamic education in responding to the challenges of the digital era. Using a qualitative library research approach, this study analyzes classical and contemporary Islamic educational thought to formulate a theological framework based on three philosophical dimensions: ontological, epistemological, and axiological. The ontological foundation emphasizes tawhid as the ultimate reality that underlies all educational activities. The epistemological dimension highlights the integration of revelation and reason as complementary sources of knowledge in Islamic education. Meanwhile, the axiological dimension focuses on the cultivation of moral character and tazkiyatun nafs as the ultimate goals of education. The findings indicate that reconstructing theological principles within Islamic education can provide meaningful orientation, strengthen digital ethics, and foster a sense of global responsibility among learners. Therefore, theological-based Islamic education offers a holistic framework to guide the use of knowledge and technology toward ethical and spiritually grounded human development.